POLA PEMBINAAN KOMPETENSI GURU MADRASAH TSANAWIYAH NEGERI PAGU KABUPATEN KEDIRI - Suseno, Hadi (Balai Diklat Keagamaan Surabaya, 2017)
Performance of teachers has not been fully supported by adequatedegree of competence, therefore there needs to be a comprehensiveeffort to improve teacher competence. To follow up the problemmentioned i n thi s research the researcher wi ll study furtherthrough empirical study by setting title: Pattern of CompetenceDevel opment of Madrasah Tsanawi yah Teachers State PaguKediri Regency. The formulation of the problem in this study asfollows: (1) How is the pattern of guidance counseling teachersMadrasah Tsanawi yah State Pagu Kedi ri through teachercompetency development ? (2) How is the pattern of guiding thecompetence of Madrasah Tsanawiyah teachers Pagu KabupatenKediri through teacher recruitment ? (3) How is the pattern of guidingthe competence of teachers of Madrasah Tsanawiyah Negeri PaguKediri through the improvement of teacher quality ? This research isdone naturally or natural, as it is, in the formal situation that is notmanipulated the circumstances and conditions and emphasizethe depiction and exposure of natural distribution data so that inthis case the researcher uses qualitative descriptive approach Thisresearch belongs to the type of qualitative research. Sources ofresearch data i s teachers MTsN Pagu Kedi ri . Data col lectiontechniques used in this study is by interview techniques, observationand documentation. communication. Then the data has beencollected analyzed by data reduction process, data presentationand conclusion. The pattern of guiding the competence of teachers ofMadrasah Tsanawiyah Negeri Pagu Kediri is done through lessonstudy activities. As an activity that begins with the development ofjoint planning, an open learning process involving a number ofobservers, and reflection or discussion after the implementation oflearning, lesson study. Is a potential activity in improving the qualityof teacher professionalism which has an impact on improvingprocess quality and learning outcomes and creating a processof interaction between various parties.